2008
DOI: 10.1590/s1980-57642009dn20200005
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge Behavioural Inventory revised

Abstract: Neurobehavioural and psychiatric symptoms are common in a range of neurodegenerative disorders with distinct profiles which are helpful in the diagnosis and monitoring of these disorders. The Cambridge Behavioural Inventory (CBI) has been shown to distinguish frontotemporal dementia (FTD), Alzheimer’s disease (AD), Huntington’s disease (HD) and Parkinson’s disease (PD), but it is lengthy.ObjectiveTo develop a shorter version of the 81 item CBI.MethodsCBI data from 450 participants with behavioural variant fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 29 publications
3
160
1
Order By: Relevance
“…All patients had been seen at the Frontier Research Clinic at Neuroscience Research Australia. Patients were included if they (i) fulfilled the criteria of PNFA, LPA [2,15] or AD [16]; (ii) had a proxy informant who could provide reliable information about the patient; (iii) did not have major depression on a screening tool [17] as well as via an interview with an expert behavioural neurologist, and (iv) had completed the Addenbrooke's Cognitive Examination Revised (ACE-R) [18,19] and Cambridge Behavioural Inventory Revised (CBI-R) [20] within 6 months of the functional assessments. Diagnoses were made by a senior neurologist after multidisciplinary input (from neuropsychologist and senior occupational therapist).…”
Section: Methodsmentioning
confidence: 99%
“…All patients had been seen at the Frontier Research Clinic at Neuroscience Research Australia. Patients were included if they (i) fulfilled the criteria of PNFA, LPA [2,15] or AD [16]; (ii) had a proxy informant who could provide reliable information about the patient; (iii) did not have major depression on a screening tool [17] as well as via an interview with an expert behavioural neurologist, and (iv) had completed the Addenbrooke's Cognitive Examination Revised (ACE-R) [18,19] and Cambridge Behavioural Inventory Revised (CBI-R) [20] within 6 months of the functional assessments. Diagnoses were made by a senior neurologist after multidisciplinary input (from neuropsychologist and senior occupational therapist).…”
Section: Methodsmentioning
confidence: 99%
“…94 The BADLS was selected as it is a well-established, validated, carer-rated instrument. It was selected as a means of gathering additional information about the extent to which participants' dementia impacted their day-to-day life.…”
Section: Functional and Behavioural Assessment Questionnairesmentioning
confidence: 99%
“…However another study found that the apathy measured with the revised version of the Cambridge behavioral inventory (CBI-R) is good indicator of survival [60].…”
Section: Accepted Manuscriptmentioning
confidence: 99%